In the Shadow of the Umbrella: U.S. Extended Deterrence and Nuclear Proliferation in East Asia, 1961-1979 - Ladha, Rizwan. (2017)
Abstract: To the extent that such they serve as effective nonproliferation tools, security guarantees are designed to put the junior ally's mind at ease about its own survival, since that is now ensured by its senior ally. Overall, such security guarantees have been remarkably useful in mitigating undesirable junior-ally behaviors and thus preventing proliferation. However, three important cases defy both historical trends and the dominant theories: Japan, South Korea, and Taiwan, each of which, despite having a bilateral security guarantee from the United States during the Cold War, went down the nuclear weapons path to some degree. Relying on an exhaustive examination of declassified U.S. archival records and utilizing qualitative process-tracing, within-case analysis, and cross-case comparison techniques, this dissertation seeks to understand what compelled these three states to venture down the nuclear weapons path, despite being under the protective wing of the United States. In the case of Japan, a deep-seated fear that the United States would abandon Japan upon the anticipated expiration of the Mutual Security Treaty in 1970, and a resurgent nationalism that invigorated a national debate on how to increase Japan's prestige in international politics, combined to compel the Japanese to conduct nuclear weapons feasibility studies in the late 1960s and then leak these studies to their American counterparts, in order to secure an extension of the Mutual Security Treaty. In the case of South Korea, a fear that the United States would fulfill its promise to remove all U.S. troops and nuclear weapons stationed on the Korean peninsula motivated Park Chung-hee to first seek a nuclear weapons arsenal and, after his efforts were discovered, then to seek a latent capability. Finally, in the case of Taiwan, the efforts of the United States to normalize relations with China and recognize Beijing, rather than Taipei, as the representative government of all of China incentivized Chiang Kai-shek and Chiang Ching-kuo to seek a latent capability rather than a functional arsenal, in order to avoid losing U.S. support altogether. At a broader level, this research finds that, consistent with more recent scholarship on alliance dynamics, junior allies can often wield outsized bargaining leverage vis-à-vis their patrons, often exploiting their senior allies' worst fears in order to advance their own self-interests. Specifically, one of the cornerstones of U.S. foreign policy since the end of World War II has been advancing the nonproliferation imperative, and U.S. allies can, under the right circumstances, win concessions from Washington by playing on its fear of horizontal proliferation. Finally, this research finds that, where a senior ally may hope to employ the security guarantee as a nonproliferation tool in the present day or in the future, there are key steps it can take to maximize its chances of success. Likewise, for a junior, non-nuclear-armed state seeking to maximize its security and ensure its survival, there are certain actions it can take with respect to its senior ally in order to achieve these self-driven interests.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Antonia Chayes.; Committee: Ian Johnstone, and Vipin Narang.; Keywords: International relations, Political science, and History.